Second Order Undamped Systems : Understanding Key Parameters - Peters, Diane L. (McGraw-Hill's AccessEngineering., 2019)
This video explains key parameters of second order undamped systems, specifically, the amplitude, period, frequency, and natural frequency. It uses a mass-spring system to show how the system behaves, and explains how to read a graph to determine these values for a system.